The Money Trap Escaping the Grip of Global Finance - Pringle, R.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The world economy is caught in a money trap. Existing monetary arrangements meet the needs neither of the ageing societies of the West nor of younger emerging economies. This in-depth analysis explains how the world got into the grip of global finance - and how it can escape, with a growing demand for reform.
Keywords: Business enterprises—Finance.; Banks and banking; Macroeconomics; Finance; Globalization; Markets; Finance, Public; Business Finance; Banking; Macroeconomics/Monetary Economics//Financial Economics; Finance, general; Emerging Markets/Globalization.; Public Finance